2023
DOI: 10.1530/raf-22-0102
|View full text |Cite
|
Sign up to set email alerts
|

The ovaries of transgender men indicate effects of high dose testosterone on the primordial and early growing follicle pool

Abstract: Androgens are essential in normal ovarian function and follicle health but hyperandrogenism, as seen in polycystic ovary syndrome, is associated with disordered follicle development. There are few data on the effect of long-term exposure to high levels of testosterone as found in transgender men receiving gender-affirming endocrine therapy. In this study, we investigate the effect of testosterone on the development, morphological health and DNA damage and repair capacity of human ovarian follicles in vivo and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…For individuals AFAB, in vitro studies have shown the teratogenicity of testosterone on fetal anatomic development, though the thresholds are not well defined and the washout period for teratogenicity is unknown. 17,22,23 Therefore, all current data suggest that retrieval of oocytes should occur before initiation of GAHT or during a period of cessation from testosterone therapy. 7,15 Studies are underway to investigate outcomes if patients are continued on testosterone during IVF.…”
Section: Fertility Preservation Genetic Parenthood and Gestational Pa...mentioning
confidence: 95%
“…For individuals AFAB, in vitro studies have shown the teratogenicity of testosterone on fetal anatomic development, though the thresholds are not well defined and the washout period for teratogenicity is unknown. 17,22,23 Therefore, all current data suggest that retrieval of oocytes should occur before initiation of GAHT or during a period of cessation from testosterone therapy. 7,15 Studies are underway to investigate outcomes if patients are continued on testosterone during IVF.…”
Section: Fertility Preservation Genetic Parenthood and Gestational Pa...mentioning
confidence: 95%